1989
DOI: 10.1073/pnas.86.7.2346
|View full text |Cite
|
Sign up to set email alerts
|

Isotype switching by a microinjected mu immunoglobulin heavy chain gene in transgenic mice.

Abstract: Immunization of transgenic mice carrying an immunoglobulin ,s heavy chain resulted in a response dominated by expression of the transgene variable region. Unexpectedly, in a large proportion of the antibody produced by immunized mice, the transgene MATERIALS AND METHODSAnimals. Transgenic C57BL/6 mice were prepared as described (13).DNA Hybridizations. DNAs digested with restriction enzymes were separated by electrophoresis through a 0.8% agarose gel, transferred to nitrocellulose, and hybridized with 32P-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 39 publications
4
50
0
Order By: Relevance
“…1) was used to produce another transgenic line (VV29). VV29 mice immunized with Ars-KLH exhibited serum levels of transgenederived anti-Ars IgG (data not shown) that were similar to previously analyzed VVC transgenic mice (25,30,31). Thus, the FIGURE 1.…”
Section: Production Of Low-copy Vvc Transgenic Mice That Exhibit Tranmentioning
confidence: 74%
See 2 more Smart Citations
“…1) was used to produce another transgenic line (VV29). VV29 mice immunized with Ars-KLH exhibited serum levels of transgenederived anti-Ars IgG (data not shown) that were similar to previously analyzed VVC transgenic mice (25,30,31). Thus, the FIGURE 1.…”
Section: Production Of Low-copy Vvc Transgenic Mice That Exhibit Tranmentioning
confidence: 74%
“…Hybridomas were initially screened for production of anti-Ars IgG using an ELISA that has previously been described (30). Anti-Ars IgG-producing hybrids were then screened for IgG reactive with the AD8 anti-idiotype again using a previously described ELISA (30). Previous studies have shown that many hybridomas from immunized VVC transgenic mice that exhibit transgene sequence transfers lack AD8 reactivity (25).…”
Section: Immunization and Hybridoma Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transchromosomal isotype switching has been reported for a number of H chain transgenes (7,8,10,(33)(34)(35)(36); however, the mechanisms involved in interchromosomal switching are not clear. Chromosomal translocations have been associated with transgene switching, and some transgene switch sites show features similar to normal class switch DNA recombinations (9).…”
Section: Discussionmentioning
confidence: 99%
“…However, in mice carrying a ,u-heavy chain transgene it has been shown that class switch could take place even when the transgene was unlinked to the IgH locus ( 14). These workers concluded that, at least in this artificial system, class switching could occur between different chromosomes and thus presumably between (Fig.…”
Section: Methodsmentioning
confidence: 99%